System gromadzenia i analizy danych czynnikiem rozwoju kapitału intelektualnego w zarządzaniu jakością - Kraus, Artur (System of Gathering and Data Analysis as a Factor of Intellectual Capital Development in Quality Management, 2008)
The article shows links and dependence between the concept of quality management and system of gathering and data analysis in intellectual capital development in an organization. The author focuses on these areas of quality management mainly concerning the monitoring and measurement process as one of basic places of functioning of quality management system. The article presents the complex system of gathering and data analysis SEWSS to be used in quality optimization. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 215-224